THE ROLE OF EDUCATION IN THE FORMATION OF COMPETITIVENESS OF STUDENT YOUTH AT THE MODERN LABOR MARKET - S. Chikaeva, Karina; V. Rachipa, Andrey; A. Karapetyan, Elena; I. Davydova, Galina; I. Kobysheva, Larisa; V. Ganshina, Galina (Gênero & Direito, 2020)
In connection with the emergence of a market environment formed in the post-Soviet period and the increasing role of innovative technologies in society, our country began to feel the need for young highly qualified personnel. In the framework of this study, the authors analyze the role of education in shaping the competitiveness of student youth in the modern labor market. Based on the methodology of the secondary analysis of empirical data, the authors show that the educational institution overcomes the existing imbalance between the structure of training in the educational system and the structure of demand in the labor market through mechanisms such as attracting employers to the educational process, cooperation with business communities, and increasing the number of credits for practice in the structure of the main professional educational program, expanding the scope of the targeted student enrollment, the use of distance Online training and courses. The article also analyzes the risks of labor integration of Russian youth.